Insulin Resistance and Skin Diseases - Maddalena Napolitano; Matteo Megna; Giuseppe Monfrecola (The Scientific World Journal)
In medical practice, almost every clinician may encounter patients with skin disease. However, it is not always easy for physicians of all specialties to face the daily task of determining the nature and clinical implication of dermatologic manifestations. Are they confined to the skin, representing a pure dermatologic event? Or are they also markers of internal conditions relating to the patient’s overall health? In this review, we will discuss the principal cutaneous conditions which have been linked to metabolic alterations. Particularly, since insulin has an important role in homeostasis and physiology of the skin, we will focus on the relationships between insulin resistance (IR) and skin diseases, analyzing strongly IR-associated conditions such as acanthosis nigricans, acne, and psoriasis, without neglecting emerging and potential scenarios as the ones represented by hidradenitis suppurativa, androgenetic alopecia, and hirsutism.